MIP-1α and MCP-1 Induce Migration of Human Umbilical Cord Blood Cells in Models of Stroke - Jiang, Lixian; Newman, Mary; Saporta, Samuel; Chen, Ning; Sanberg, Cyndy; Sanberg, Paul R.; Willing, Alison E. (Current Neurovascular Research, 2008)
Monocyte chemoattractant protein-1 (MCP-1) and macrophage inflammatory protein (MIP-1α) are implicated in monocyte infiltration into the central nervous system (CNS) under pathological conditions. We previously showed that in vivo human umbilical cord blood cells (HUCB) migrate toward brain injury after middle cerebral artery occlusion (MCAO). We hypothesized that MCP-1 and MIP-1α may participate in the recruitment of HUCB towards the injury. Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO), and 24 hours later the production of MCP-1 and MIP-1α in the brain was examined with immunohistochemistry, ELISA, and western blotting. The chemotactic effect of MCP-1 and MIP-1α, and the expression of MCP-1 receptor CCR2 and MIP-1α receptor CCR1, CCR5 on the surface of HUCB were also examined. MCP-1 and MIP-1α expression were significantly increased in the ischemic hemisphere of brain, and significantly promoted HUCB cell migration compared to the contralateral side. This cell migration was neutralized with polyclonal antibodies against MCP-1 or MIP-1α. Also chemokine receptors were constitutively expressed on the surface of HUCB cells. The data suggested that the increased chemokines in the ischemic area can bind cell surface receptors on HUCB, and induce cell infiltration of systemically delivered HUCB cells into the CNS in vivo.
Keywords: migration